Dynamic of arm’s micro movements of elite athlete in Olympic exercises Rapid Fire Pistol and Air Pistol - V.T. Pyatkov; J. Bilinski; O.S. Petriv; T.M. Magmet (Physical Education of Students, 2017)
Purpose: to scientifically substantiate the method of contactless determination of athlete hand’s movements in Olympic exercises with pistol. Material: in the research we used the data of 37 elite athletes in exercise Air Pistol (n=32) and in exercise Rapid Fire Pistol (n=5). Registration of pistol projection’s quickness of movement in target area was realized with the help of computer system Scatt. In total we analyzed 3100 space-time parameters of athletes’ technical-tactic actions in finalizing phase of shooting cycle. Results: we tested innovative method of contactless measuring of athlete’s hand’s micro movements in finalizing phase of shooting cycle. We found uncontrolled deviations from optimal pistol pointing position in vertical, horizontal and sagittal planes. Quickness of athlete hand’s movements in shooting process was determined. Conclusions: we scientifically substantiated the method of contactless determination of athlete hand’s movements at a distance in Olympic exercises with pistol. Besides, we determined the dynamic of athlete’s hand micro movements in Olympic exercises Rapid Fire Pistol та Air Pistol.